Applications of WDM System in US Patents - Mhnd Farhan (Program Studi Teknik Informatika Universitas Paramadina, 2026)
In fiber-optical telecommunications, wavelength division multiplexing (WDM) is a multiplexing and transmission scheme in which distinct wavelengths, each emitted by multiple lasers, carry specific information. WDM filters are used to multiplex these wavelengths. Similarly, at the receiving end, they are demultiplexed or separated using coherent detection with tunable local oscillators or similar filters. This paper explains the most recent applications of the WDM System in US patents. A succinct explanation of the WDM System is also given.